2019
DOI: 10.1088/1742-6596/1179/1/012153
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis Of The Effectiveness Of School-Base Reproductive Health Promotion Programs For Early Adolescents

Abstract: Religiosityis one of protective factor toward adolescents’ risked behavior. It is so important to teach them the religious value to family. The understanding of reproductive health will be easier to be received by adolescents and society if the process of delivering the content always consider the values and norm held by society. The previous research finding has been developed to a school-based reproductive health promotion for younger adolescents who have not faced akhil baliq (menarche or semenarche)with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Sexual education is not only about the stages of adult sexual intercourse, but more important than that is education about integration of feelings, body parts that must be protected from unwanted touches, physical changes, mental and emotional changes, hygiene during menstruation and self-care related to the development of sex secondary to adolescents. 12,39 Some efforts that parents can do are still limited to general activities such as prohibiting children from engaging in sexual acts. In expressing the feelings of adolescents with ASD towards the opposite sex and mentioning body parts that should not be touched by others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual education is not only about the stages of adult sexual intercourse, but more important than that is education about integration of feelings, body parts that must be protected from unwanted touches, physical changes, mental and emotional changes, hygiene during menstruation and self-care related to the development of sex secondary to adolescents. 12,39 Some efforts that parents can do are still limited to general activities such as prohibiting children from engaging in sexual acts. In expressing the feelings of adolescents with ASD towards the opposite sex and mentioning body parts that should not be touched by others.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescence, an individual with ASD will experience sexual development that is no different from adolescents in general, such as secondary sex development, namely hair growth in the armpits, genitals, mustache, nocturnal orgasm in boys and menstruation in girls. 4,[10][11][12] ASD is a comprehensive developmental disorder that occurs in children that affects the skills of thinking, behaving, behaving and repeating movements with an increase in the incidence of the fastest cases in the world. 9,[13][14][15][16] Data from WHO in 2019 revealed that at present 1 out of 160 children in the world is detected ASD.7 This data is supported by a report from the CDC in 2018 which revealed that currently there has been an increase of 15% in the world's ASD population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation